Environmental Sustainability through Solid Waste Management - Ravichandran, S (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 11 No 1&2 (2024): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2024)
The United States of Americaâ€™s (USA) Environmental Protection Agency defines The term â€œsolid wasteâ€ refers to any trash or refuse, sludge from a water treatment plant, wastewater treatment plant, air pollution control facility, or other material that has been discharged as a result of community, commercial, mining, industrial, or agricultural operations. Solid trash is the leftover solid material from commercial, industrial, residential, and other operations. Examples of solid garbage include plastic, paper, metal, organic waste, glass, hazardous materials, industrial waste, and household waste. The only factors contributing to the high rate of solid waste increase are urbanisation and population growth, and municipal corporations face significant challenges in properly managing this waste. This study focused on the detrimental impact of inadequate waste management on health. The outcome demonstrates that solid waste from homes and communities poses a major risk to public health and contributes negatively to the spread of infectious diseases. Establishing a framework that guarantees a sustainable approach to solid waste management for the benefit of both current and future generations while simultaneously addressing the issues of the present is the ultimate goal.